Cooperative adsorption of carbon disulfide in diamine-appended metal–organic frameworks. Issue 1 (December 2018) - McGuirk, C.; Siegelman, Rebecca; Drisdell, Walter; Runčevski, Tomče; Milner, Phillip; Oktawiec, Julia; Wan, Liwen; Su, Gregory; Jiang, Henry; Reed, Douglas; Gonzalez, Miguel; Prendergast, David; et al.
Abstract Over one million tons of CS2 are produced annually, and emissions of this volatile and toxic liquid, known to generate acid rain, remain poorly controlled. As such, materials capable of reversibly capturing this commodity chemical in an energy-efficient manner are of interest. Recently, we detailed diamine-appended metal–organic frameworks capable of selectively capturing CO2 through a cooperative insertion mechanism that promotes efficient adsorption–desorption cycling. We therefore sought to explore the ability of these materials to capture CS2 through a similar mechanism. Employing crystallography, spectroscopy, and gas adsorption analysis, we demonstrate that CS2 is indeed cooperatively adsorbed inN, N -dimethylethylenediamine-appended M2 (dobpdc) (M = Mg, Mn, Zn; dobpdc4- = 4, 4′-dioxidobiphenyl-3, 3′-dicarboxylate), via the formation of electrostatically paired ammonium dithiocarbamate chains. In the weakly thiophilic Mg congener, chemisorption is cleanly reversible with mild thermal input. This work demonstrates that the cooperative insertion mechanism can be generalized to other high-impact target molecules. The large-scale production of CS2 presents both environmental and biological hazards, yet adsorbents capable of CS2 capture remain scarcely explored. Here, Long and colleagues demonstrate that CS2 is adsorbed in diamine-appended metal–organic frameworks through a cooperative and chemically specific insertion process.